Views of the General Population on Newborn Screening for Spinal Muscular Atrophy in Japan - Tomoko Lee; Sachi Tokunaga; Naoko Taniguchi; Tetsuro Fujino; Midori Saito; Hideki Shimomura; Yasuhiro Takeshima (MDPI AG, 2021)
Spinal muscular atrophy (SMA) is a genetic neuromuscular disorder that results in progressive muscle atrophy and weakness. As new therapies for SMA have been developed, newborn screening for SMA can lead to early diagnosis and treatment. The objective of this study was to gather the general population's view on screening of SMA in newborns in Japan. A questionnaire survey was conducted on two general population groups in Japan. A total of 269 valid responses were obtained. In the general population, about half of the participants had no knowledge about SMA, and more than 90% did not know about new therapies for SMA. Conversely, more than 95% of the general population agreed with screening newborns for SMA because they believed that early diagnosis was important, and treatments were available. This study revealed that the general population in Japan mostly agreed with screening for SMA in newborns even though they did not know much about SMA. Newborn screening for SMA is promising, but it is in very early stages. Therefore, SMA newborn screening should be performed with sufficient preparation and consideration in order to have a positive impact on SMA patients and their families.